Combined therapy using bevacizumab and turmeric ethanolic extract (with absorbable curcumin) exhibited beneficial efficacy in colon cancer mice. (September 2016) - Yue, Grace Gar-Lee; Kwok, Hin-Fai; Lee, Julia Kin-Ming; Jiang, Lei; Wong, Eric Chun-Wai; Gao, Si; Wong, Hing-Lok; Li, Lin; Chan, Kar-Man; Leung, Ping-Chung; Fung, Kwok-Pui; Zuo, Zhong; et al.
Graphical abstract: Abstract: Turmeric is commonly used as a medicinal herb and dietary supplement. Its active ingredient, curcumin, has been shown to possess antitumor effects in colorectal cancer patients. However, poor absorption of curcumin in intestine impedes its wide clinical application. Our previous findings showed that the presence of turmerones increased the accumulation of curcumin inside colonic cells. Hence, we hypothesized that curcumin with turmerones or present in turmeric ethanolic extract would augment its anti-tumor activities in tumor-bearing mice. The pharmacokinetics of curcumin in different preparations (containing same amount of curcumin) were studied in mice. The anti-tumor efficacies of curcumin or turmeric extract (with absorbable curcumin) in combination with bevacizumab were further investigated in HT29 colon tumor-bearing mice. Pharmacokinetic results showed that the plasma curcumin level of turmeric extract-fed mice was the highest, suggesting turmeric extract had the best bioavailability of curcumin. Besides, combined turmeric extract plus bevacizumab treatment significantly inhibited the tumor growth. Such inhibitory effects were stronger than those of curcumin plus bevacizumab or bevacizumab alone and were comparable with those of 5-fluorouracil + leucovorin + oxaliplatin (FOLFOX) plus bevacizumab. Notably, there was no observable side effect induced by turmeric extract treatment while significant side effects were found in FOLFOX-treated mice. In conclusion, combination of turmeric extract with bevacizumab possessed potent anti-tumor effects without observable side effects, strongly suggesting the adjuvant use of turmeric extract in colorectal cancer therapy. Our current findings warrant the confirmation regarding the benefits arising from the combined use of bevacizumab and turmeric in colorectal cancer patients in the near future.